Effects of essential oils on native and recombinant acetylcholinesterases of Rhipicephalus microplus - Santos,Everton Gomes Guimarães dos (2021)
Abstract This study reports the action of essential oils (EO) from five plants on the activity of native and recombinant acetylcholinesterases (AChE) from Rhipicephalus microplus. Enzyme activity of native susceptible AChE extract (S.AChE), native resistant AChE extract (R.AChE), and recombinant enzyme (rBmAChE1) was determined. An acetylcholinesterase inhibition test was used to verify the effect of the EO on enzyme activity. EO from Eucalyptus globulus, Citrus aurantifolia, Citrus aurantium var.dulcis inhibited the activity of S.AChE and R.AChE. Oils from the two Citrus species inhibited S.AChE and R.AChE in a similar way while showing greater inhibition on R.AChE. The oil from E. globulus inhibited native AChE, but no difference was observed between the S.AChE and R.AChE; however, 71% inhibition for the rBmAChE1 was recorded. Mentha piperita oil also inhibited S.AChE and R.AChE, but there was significant inhibition at the highest concentration tested. Cymbopogon winterianus oil did not inhibit AChE. Further studies are warranted with the oils from the two Citrus species that inhibited R.AChE because of the problem with R. microplus resistant to organophosphates, which target AChE. C. winterianus oil can be used against R. microplus populations that are resistant to organophosphates because its acaricidal properties act by mechanism(s) other than AChE inhibition.